Demographic determinants of hardcore urban poverty in Malaysia / Nurliana Athirah Ramlan and Nur Shafikah Azlin Johari - Ramlan, Nurliana Athirah; Johari, Nur Shafikah Azlin (2019)
Malaysia is one of the Asian countries that has increasingly advanced in development of country from year to year in accordance with the passage of time. However, lately urban poverty in Malaysia becomes a phenomenon because of the impacts of the urbanization. The population migration from rural to urban areas also contributed to the acceleration of urbanization. Since the issues of urban poverty has been rise up, it is important to determine the factor that influence of hardcore urban poverty in Malaysia. In this study, the secondary data (Household Income Survey 2012) extracted from Department of Statistic Malaysia (DOSM) was utilized. For this study, the statistical analysis that have been applied are Chi-Square Test of Association, Binary Logistic Regression and Odds Ratio in order to achieve the objectives of this study. Based on the results of the logistic regression, this study found that only marital status of head of households and education level of head of households are the factors that affecting to hardcore urban poverty. As conclusion, there is significant effect towards hardcore urban poverty but in this study only marital status and education level is significant. Therefore, for the future study it needs some improvement. This study should include more variable that may have possibility affect to the hardcore urban poverty